Efektivitas Pengelolaan Zakat Pada Umkm Kabupaten Tulungagung - Ahmad Hamizah, (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2023)
Zakat can function as a source of socio-economic funds for Muslims. the use of zakat managed by the Amil Zakat institution is not limited to certain activities based on conventional orientation, but can also be used for people's economic activities, such as poverty and unemployment alleviation programs by providing productive zakat to those in need as commercial capital. This article aims to determine the effectiveness of Zakat management by the Tulungagung Regency National Amil Zakat Agency, using a qualitative approach and a descriptive type. Sources of data obtained from observations through observation, interviews, and documentation. While the analysis technique used goes through the selection stage of the main points and important things in the field, so that the data presentation can be understood in the cases that were studied at that time. Zakat management carried out by BAZNAS Tulungagung Regency, especially in collecting zakat funds has not shown optimal results, with this kind of thing it certainly makes zakat managers innovate in introducing how this zakat is distributed and can become one of the instruments that can contribute to the regional economy so that national.